2016
DOI: 10.1177/0884533615627266
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia, Hypomagnesemia, and Hypokalemia in Pediatric Patients Before and During Exclusive Individualized Parenteral Nutrition

Abstract: Hypophosphatemia, hypokalemia, and hypomagnesemia were frequent in hospitalized pediatric patients before and during the first 4 days of PN infusion. Patients with malnutrition had more chances of having hypokalemia, and those who received high protein infusion had an increased chance of developing hypomagnesemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Reported that hypokalemia is associated with poor nutritional status in ambulatory peritoneal dialysis patients. Patients with malnutrition increased risk of hypokalemia because of insufficient intake, excessive loss and electrolyte distribution (Hortencio et al, 2016). Furthermore, low levels of APTT, EOS, and PCT reflecting the status of coagulopathy or anemia were significantly associated with postoperative hypokalemia in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Reported that hypokalemia is associated with poor nutritional status in ambulatory peritoneal dialysis patients. Patients with malnutrition increased risk of hypokalemia because of insufficient intake, excessive loss and electrolyte distribution (Hortencio et al, 2016). Furthermore, low levels of APTT, EOS, and PCT reflecting the status of coagulopathy or anemia were significantly associated with postoperative hypokalemia in this study.…”
Section: Discussionmentioning
confidence: 47%
“…1,2,[11][12][13][14] This difference may have occurred because, in general, most studies did not exclude patients receiving PN, and this nutrition route is known to be related to a decrease in serum phosphorus levels in children and adult patients. 9,10 The rarity of HPr and severe HP cases observed in our study may be related to our exclusion of patients receiving PN, in whom such complications are known to commonly occur. 9 We believe that frequent monitoring of serum phosphorus levels and prompt replacement may help detect mild HP and prevent severe HP.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies with critically ill pediatric patients show an even higher incidence of HP (42.0%–79.5%) 1,2,11–14 . This difference may have occurred because, in general, most studies did not exclude patients receiving PN, and this nutrition route is known to be related to a decrease in serum phosphorus levels in children and adult patients 9,10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However RS was more rigorously defined not only by the finding of hypophasphatemia [ 39 ]. Data collected retrospectively on children in the same year showed that hypophosphatemia, hypokalemia and hypomagnesimia were frequent in children receiving inpatient PN before and during the first four days after starting PN [ 40 ] . Malnourished children in this cohort were found to be more prone to develop low levels of potassium, wheras patients who received a high intravenous protein load had a higher incidence of hypomagnesaemia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%